Sow, grow, and thrive: a pathway to improve cassava farming in Zambia - Kudzanai Chimhanda (International Maize and Wheat Improvement Center, 2024)
SIFAZ is shifting farmer mindsets towards promoting sustainable practices that not only improve cassava yields but minimize physical labor.